2013
DOI: 10.1186/1467-4866-14-4
|View full text |Cite
|
Sign up to set email alerts
|

A new model for the biodegradation kinetics of oil droplets: application to the Deepwater Horizon oil spill in the Gulf of Mexico

Abstract: Oil biodegradation by native bacteria is one of the most important natural processes that can attenuate the environmental impacts of marine oil spills. Existing models for oil biodegradation kinetics are mostly for dissolved oil. This work developed a new mathematical model for the biodegradation of oil droplets and applied the model to estimate the time scale for oil biodegradation under conditions relevant to the Deepwater Horizon oil spill in the Gulf of Mexico. In the model, oil is composed of droplets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…The introduction of chemical dispersants reduced the surface tension of the oil and created droplets smaller than those formed by natural dispersions or releases from natural seeps. The small size of the oil droplets formed also increased the surface area available for microbial colonization, and significantly enhanced the biodegradation; one of the most important process for the removal of the oil released from the DWH spill and retained in the water column (Atlas and Hazen, 2011;Meckenstock et al, 2014;Vilcaez et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The introduction of chemical dispersants reduced the surface tension of the oil and created droplets smaller than those formed by natural dispersions or releases from natural seeps. The small size of the oil droplets formed also increased the surface area available for microbial colonization, and significantly enhanced the biodegradation; one of the most important process for the removal of the oil released from the DWH spill and retained in the water column (Atlas and Hazen, 2011;Meckenstock et al, 2014;Vilcaez et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…With the advent of technologies that allow oil recovery from hundreds of meters below the sea surface, a better understanding of oil droplet formation, evolution, transport, and degradation in deep waters is necessary to predict the fate and transport of subsurface oil spills (Yapa et al 2012). In addition, this information is necessary to fully understand the impact of dispersants applied at the wellhead which greatly affects droplet sizes , Vilcáez et al 2013, Nagamine 2014 and to better constrain the estimate of the mass of initially suspended droplets in deep hydrocarbon plumes, which is one of the largest uncertainties in the hydrocarbon budget of the Deepwater Horizon (DH) spill (Ryerson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On water surface, the spilled oil is commonly dispersed into small droplets, which are then decomposed naturally by microorganisms. However, model prediction [2] and lab-scale reactors [3] have indicated that this process can take up to few months, during which the oil droplets can have adverse impacts on marine habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the oil droplets can concentrate in certain area of the marine system and signify the environmental impacts locally. The effective bio-degradation process also requires nutrients [2] which are limited in water bodies. Most critically, dispersing process relies on dispersants, which can be more toxic than the oils themselves [6].…”
Section: Introductionmentioning
confidence: 99%